1984
DOI: 10.1176/appi.psychotherapy.1984.38.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Suicide in Manic-Depressive Disorder

Abstract: Structured interviews were used to study rates of past suicide attempts among 123 outpatients treated for affective disorders. Subjects met the Feighner criteria for major affective illness, and bipolar and unipolar groups were identified in accordance with the Fieve-Dunner criteria. Although a small group (N = 6), the women with a history of hospitalization for depression and outpatient treatment for hypomania (BP II) had the highest rate of past suicide attempts. (66 percent). This confirms previous findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Although we made no distinction between attempts and completed suicides for the purposes of this investigation, we acknowledge the potential significance of differences between these manifestations of suicidal behavior. For instance, other studies have demonstrated that bipolar women attempt suicide more frequently than men (49, 50), though men tend to succeed more frequently (19), a finding demonstrated in our data as well. However, some of these results show only statistical trends.…”
Section: Discussionsupporting
confidence: 87%
“…Although we made no distinction between attempts and completed suicides for the purposes of this investigation, we acknowledge the potential significance of differences between these manifestations of suicidal behavior. For instance, other studies have demonstrated that bipolar women attempt suicide more frequently than men (49, 50), though men tend to succeed more frequently (19), a finding demonstrated in our data as well. However, some of these results show only statistical trends.…”
Section: Discussionsupporting
confidence: 87%
“…Bipolar II disorder and highly recurrent depression are closely related (610). Bipolar II disorder appears to be associated with a significant risk of suicide (614–617). Patients with a diagnosis of bipolar II disorder are more likely to have demonstrated an earlier age of onset, have a family history of bipolar II, and will experience higher rates of recurrence, anxiety disorders and substance abuse compared to patients with MDD (76, 609, 610, 618, 619).…”
Section: Section 7: Bipolar II Disorder: Acute and Maintenance Managementioning
confidence: 99%
“…Several studies have reported a higher risk of suicide in bipolar II patients (63, 91–93). Rihmer and Pestality (94) reviewed the rate of lifetime history of suicide attempts and found it was attempted by 17% of bipolar I patients, 24% of bipolar II patients, and 12% of unipolar major depressive patients.…”
Section: Longitudinal Coursementioning
confidence: 99%